2022
DOI: 10.1155/2022/7881717
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Oxidative Stress in the Pathogenesis and Treatment of Hyperpigmentation Disorders

Abstract: Oxidative stress represents an imbalance between the generation of reactive oxygen and nitrogen species and the ability of antioxidant systems to decompose those products. Oxidative stress is implicated in the pathogenesis of hyperpigmentation, hypopigmentation, melanoma, and other skin diseases. Regulatory networks involving oxidative stress and related pathways are widely represented in hypopigmentation diseases, particularly vitiligo. However, there is no complete review into the role of oxidative stress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 114 publications
0
23
0
Order By: Relevance
“…2 Previous studies have shown that exposure to ultraviolet radiations can result in tanning or hyperpigmentation of the human skin. 3 Interestingly in this study, the novel grapeseed oil-loaded dermocosmetic nanoemulgel resulted in continuous and statistically significant decline in skin melanin levels. Grapeseed oil is rich in phenolic compounds and flavonoids.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…2 Previous studies have shown that exposure to ultraviolet radiations can result in tanning or hyperpigmentation of the human skin. 3 Interestingly in this study, the novel grapeseed oil-loaded dermocosmetic nanoemulgel resulted in continuous and statistically significant decline in skin melanin levels. Grapeseed oil is rich in phenolic compounds and flavonoids.…”
Section: Discussionmentioning
confidence: 56%
“…Symptoms of this damage include erythema, inflammation, pigmentation, coarseness, wrinkles, and dryness. 2,3 Previous studies have shown that exposure to ultraviolet radiation increases the generation of free radicals. These highly reactive intermediate compounds were shown to increase the production of inflammatory mediators like interleukins and cytokines, which in turn, cause erythema and inflammation of the skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solamargine (SM), a steroidal alkaloid glycoside extracted from Solanum undatum , has been proven to have anti-inflammatory, antioxidant and anti-tumor effects. Studies have shown that SM can exert anti-tumor effects ( Figure 1A ) by up-regulating the expression of TNF-α1 and TNF-α2 and activating caspase-3 to cause tumor cells apoptosis ( 12 , 13 ); it can exert potent anti-inflammatory effects by inhibiting the NF-κB/p65 pathway and inhibiting the expression of COX-2 ( 14 , 15 ). In addition, SM can exert some antioxidant effects by reducing ROS release and down-regulating the activity of i-NOS ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species increase pigmentation and cause oxidative stressinduced damage to the melanocytes 3 . Hyperpigmentation disorders are diseases in which patches of skin are darker than the normal surrounding skin, resulting from the upregulated activity of melanin synthesis, increased numbers of melanocytes, and decreased decomposition of melanosomes 4 . Hyperpigmentation conditions can also be caused by certain drugs, hormonal changes, or autoimmune conditions 5 .…”
Section: Introductionmentioning
confidence: 99%